The Mongol invasions of Central Asia - Islam, Arshad (2014)
The Mongol invasions of Central Asia were the greatest catastrophe in the history of Islamic civilization, laying waste to the global centre of intellectual achievement during the 11th to 13th centuries. The classical Islamic civilization of the dawlatayn (Umayyad and Abbasid dynasties) had continued in one form or another into the early 12th century, supporting the famous blossoming of culture and science which gave birth to the modern world during the European Renaissance. This paper explores the causes and consequences of the Mongol invasions based on Persian, Arabic, Urdu and English sources. It finds that the Mongols were dismissed by the Muslim elite in Central Asia, particularly the Khwarazm Shah and his court, as a barbaric horde that posed no significant threat to them. It finds that the sophisticated system of Mongol propaganda was so effective that the myths it propagated are widely believed to this day, with emotive imagery such as the Tigris running red with the blood of the Muslims and black with the ink of their scholars, as Chengis Khan and his successors unleashed an unstoppable force of nature to destroy civilization. Conversely, the study concludes that the causes of the Mongol invasions were more related to the weaknesses and incompetence of the Central Asian civilization than to the inherent strength of the Mongol invaders, and furthermore that the Islamic civilization was already waning before their arrival in Otrar. It concludes that the Mongol invasions, although initially catastrophic for Central Asia, as with most invasions, ultimately led to the integration of the Mongols into Islamic civilization (like the Ghaznavids and Seljuqs before them) and gave a new impetus to life and culture in the region later expressed in the Timurids and Mughals. It finds that the Mongols represented a later manifestation of the ancient phenomenon of nomadic invaders of decadent civilizations giving a new course and direction to the latter, as recognised in ‘pre-Islamic' Persian sources and identified in Islamic sociology by Ibn Khaldun. Keywords: Umayyads, Abbasids, Mongols, Chengis Khan, Ghaznavids, Seljuqs, Khwarazm Shah, Timurids, Mughals.